O ensino da agroecologia nas Escolas Família Agrícolas do Estado de Goiás: que agroecologia é essa? - Amaral, Ana Paula do (2019)
This thesis refers to the problem of teaching agroecology in the Family Agricultural Schools (EFAs- Escola Família Agrícola) in the state of Goiás. In these schools, the pedagogical work is carried out under alternating conditions due to different times and educational spaces, combining a period of activities at the school and a period of activities at the rural property, generally known as the School Session and the Family Session, respectively. Based on the presumption that agroecology is increasingly present in these schools and in various spaces of the self-organization the working class, essentially as a critic for conventional agriculture and livestock, this work aimed to analyze its epistemological bases and the consequent implications in the process of youth formation in rural areas. It seeks to investigate the concepts of education and agroecology contained in the Political-pedagogical projects, in the Statutes of the supporting associations, as well as in the statements of pedagogical coordinators, directors, association leaders, technical professors and graduates of these EFAs. Thus, this thesis is able to explicitly demonstrate how agroecology is being constituted in these schools through the curriculum of the pedagogy of alternating locations and in what way these repercussions affect the formation of young people. The instruments used in this research include documentary analysis, interviews and field observations of farming and livestock practices carried out on the school properties and with the graduates interviewees. In addition, this thesis questions the possibilities of scientific appropriation and technique in the Integrated High School (Ensino Médio Integrado) Program through agroecology, especially given this moment of structural crises of the capitalist system. This thesis verifies the hypothesis that, regardless of the scientific advances in the field of agroecology, the way that it is interpreted by the subjects is philosophically approximated to phenomenological existentialism and pragmatism, which in most cases limits an understanding of reality as a concrete totality.